Um estudo sobre bullying entre escolares do ensino fundamental - Francisco, Marcos Vinicius [UNESP]; Libório, Renata Maria Coimbra [UNESP] (Curso de Pós-Graduação em Psicologia da Universidade Federal do Rio Grande do Sul, 2009)
This research, of quali-quantitative nature, had the aim of characterizing the phenomenon of bullying in two state public schools of Presidente Prudente-SP through the use of questionnaires applied to two hundred eighty-three students of 5th and 8th grades. It was taken into consideration frequency, gender, most common places and ages of bullying prevalence, students' place of living, effects on the behavior and the feelings of the victim, as well as the opinion of the participants about facing the problem. The questionnaire used was based on studies of Elliot (1992) and Olweus (1991). The results were likely to characterize the dimensions of bullying in the studied reality, what allowed us to confirm its presence in the school environment, requesting more attention from the education professionals concerning the phenomenon.

A presente pesquisa, de natureza quali-quantitativa, teve como objetivo caracterizar o bullying em duas escolas públicas estaduais de Presidente Prudente-SP, através da aplicação de questionários semi-aberto, em duzentos e oitenta e três alunos de 5as e 8as séries, quanto à: freqüência, gênero, local e idades prevalecentes de acometimento do bullying, tipos, local de residência do aluno, efeitos sobre o comportamento e sentimentos do vitimizado, e opiniões dos participantes sobre o enfrentamento do problema. O questionário utilizado baseou-se em estudos de Elliott (1992) e Olweus (1991). Os resultados permitiram caracterizar as dimensões do bullying na realidade estudada, bem como constatar sua presença no ambiente escolar, o que requer mais atenção dos profissionais da educação para o enfrentamento do fenômeno.
A study on bullying victimization among peers in elementary and junior high school
Keywords: Bullying; violence; students; Bullying; violência; escolares